Extraction and characterization of polysaccharides and phenolic compounds from spent coffee grounds and their incorporation into edible films/coatings for food applications - Giraldo, Lina Fernanda Ballesteros (2016)
Tese de Doutoramento dem Engenharia Química e Biológica.